Introduction to the music industry : an entrepreneurial approach - Fitterman Radbill, Catherine (Routledge, 2017)
Introduction to the Music Industry: An Entrepreneurial Approach, Second Edition is an introductory textbook that offers a fresh perspective in one of the fastest-changing businesses in the world today. It engages students with creative problem-solving activities, collaborative projects and case studies as they explore the inner workings of the music business, while encouraging them to think like entrepreneurs on a path toward their own successful careers in the industry. This new edition includes a revised chapter organization, with chapters streamlined to focus on topics most important to music business students, while also maintaining its user-friendly chapter approach. Supported by an updated companion website, this book equips music business students and performance majors with the knowledge and tools to adopt and integrate entrepreneurial thinking successfully into practice and shape the future of the industry.